The Psychological Security of Students in the Kindergarten Department (Journal Of Educational and Psychological Researches, 2023)
AbstractThe current research aims to identify the psychological security of students in the kindergarten department and identify if there is a significant difference between stage one and stage four students. To do this, the researcher adopted the psychological research scale of (Al-mohamdawi, 2007) that consisted of (30) items. It was administered to (120) female students chosen randomly from the kindergarten department in the college of education for women for the academic year (2029-2021). The results revealed that students in the kindergarten department have psychological security. There is a significant difference between stage one and four students in favor of stage four students.